Stochastic dynamic response and seismic reliability analysis of nuclear power plant's vertical retaining wall based on plastic failure. (June 2021) - Zhou, Yang; Jing, Mingyuan; Pang, Rui; Xu, Bin; Jiang, Feng; Yu, Xiang
Abstract: Vertical retaining wall is usually built at the water intake in front of the pump station and is widely used in the protection of intake and voidance structures of nuclear power plants (NPPs). It has great practical significance for disaster prevention to gauge the plastic failure of vertical retaining wall accurately. In this paper, a generalized plastic model is introduced to obtain the residual deformation of vertical retaining wall during earthquake and the numerical simulation results based on plastic model reflect the plastic failure mode of the vertical retaining wall, which is consistent with the shaking table test results. In addition, the seismic excitation has great uncertainty, and in order to reflect the uncertainty, a set of fully nonstationary stochastic seismic loading samples are generated with spectral representation random function method. As a recently developed dynamic reliability methodology, the probability density evolution method (PDEM) is incorporated to the generalized plastic model to perform stochastic seismic response analysis of a vertical retaining wall. Plentiful probabilistic results of vertical retaining wall, such as evolution of probability density functions (PDF) and second-order statistics are acquired in this study. Finally, the dynamic reliability of vertical retaining wall under two earthquake levels are obtained based on the dip angle, which can more directly reflect the failure probability and degree of vertical retaining wall. The results of this study indicate that the geotechnical structures can show a more objective failure mode under earthquakes based on the plastic model, and it is more reliable to evaluate the safety of structures from the perspective of probability combined with PDEM.